Antyk jako źródło wzorów wychowawczych i edukacyjnych w Polsce czasów rozbiorowych = About role models derived from classical authors in the 18th- and 19th-century Poland - Brzuska, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The nineteenth century in Poland brought about a surge in the number of translations from Latin and Greek, which resulted from the diminishing number of people who were able to read Greek and Latin classics in the original languages, on the one hand, and on a widely held conviction about extraordinary formative qualities of this literature in the process of educating young people, on the other.
Keywords: literatura starożytna; Translatoryka; wzory osobowe; postawy obywatelskie; bohaterowie i antybohaterowie z antyku; Polska; 18 w.; 19 w.; literature of Antiquity; translations; role models and examples; heroes and anti-heroes from Antiquity; Poland